Law Enforcement On The Safeguarding Of Evidence That Has Become Legally Binding (In Kracht Van Gewijsde) In Corruption Crimes (A Study At The Attourney’s Office Of South Tapanuli District) - Stiven Jhasen Sinaga; Suci Ramadani; Ismaidar Ismaidar (JURNAL HUKUM SEHASEN, 2026)
Corruption is a form of crime that has a direct impact on the welfare of society. Corruption is an unlawful act carried out to enrich oneself, another person, or a corporation, which is detrimental to state finances or the country's economy. Corruption is also a crime that is included in the category of special crimes because it has different specifications from general crimes both in procedural law and material (substance), especially in the handling of evidence of special crimes whose origins must be examined so that the handling of the crime does not harm parties who are not involved. Corruption is also regulated in various regulations such as Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, Law Number 15 of 2002 concerning the Crime of Money Laundering, Law Number 30 of 2002 concerning the Corruption Eradication Commission, the latest Criminal Code (Law Number 1 of 2023), and so on. The law has regulated a number of provisions aimed at strengthening and perfecting the eradication of corruption in Indonesia as well as anticipating and eradicating various increasingly sophisticated corruption modes, as well as increasing the effectiveness of law enforcement related to corruption crimes. The method used is an empirical juridical approach with direct field research studies at the South Tapanuli District Attorney's Office. Mechanisms and Procedures for Securing Evidence in Corruption Crimes according to the provisions of the Criminal Procedure Code and the Corruption Crime Law. The provisions of evidence according to the Criminal Procedure Code are regulated in articles 39-46 of the Criminal Procedure Code starting from Confiscation, Storage of Confiscated Objects, Management of Confiscated Objects / evidence after having permanent legal force. Meanwhile, Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Corruption Crimes regulates more specifically the management of evidence, especially related to assets resulting from corruption by means of Asset Confiscation (Article 18 of the Corruption Law). Confiscation of Assets suspected of originating from criminal acts of corruption, Blocking and Custody, to Execution of Decisions. The Role of the Prosecutor's Office in Securing Evidence that has been In Kracht in corruption cases. The Prosecutor's Office through the Asset Recovery and Evidence Management division has a role in managing evidence as regulated in the Regulation of the Attorney General of the Republic of Indonesia Number: PER-027/A/JA/10/2014 Concerning Guidelines for Asset Recovery. In practice, the management of evidence carried out by the Prosecutor's Office through the Asset Recovery and Evidence Management Division consists of 5, namely: Direct Sales, Indirect Sales, Determination of Use Status, Grants, and Destruction. Implementation of Evidence Securing in the Practice of Corruption Law Enforcement at the South Tapanuli District Prosecutor's Office. Evidence Securing in criminal acts of corruption at the South Tapanuli District Prosecutor's Office often takes the form of documents, financial transactions, and letters.